Green synthesis of silver nanoparticles using aqueous leaf extract of Saussurea obvallata for efficient catalytic reduction of nitrophenol, antioxidant, and antibacterial activity - Vidya Sagar, P.S.R.; Ramadevi, Dharmasoth; Basavaiah, Keloth; Botsa, Sathish Mohan (Water Science and Engineering, 2024)
Of several noble metal nanoparticles, silver nanoparticles (AgNPs) have attracted special attention due to their distinct properties, such as favorable electrical conductivity, chemical stability, and catalytic and antibacterial activities. Green synthesis of AgNPs using plant extracts containing phytochemical agents has attracted considerable interest. This environmentally friendly approach is more biocompatible and cost-efficient and has the capability of supporting large-scale synthesis. This study developed an eco-friendly method for the preparation of AgNPs using the aqueous leaf extract of Saussurea obvallata as reducing and capping agents. Ultraviolet visible spectroscopy (UV–Vis), Fourier transform infrared spectroscopy (FTIR), Raman, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) analyses were conducted to characterize the synthesized AgNPs. The morphology of AgNPs was found to be spherical with an average crystallite size of 12 nm and a maximum absorbance at 410 nm. 10 mg of AgNPs had potential to reduce 4-nitrophenol to 4-aminophenol in 16 min and exhibited strong biological activities against the Gram-negative bacteria Escherichia coli (12 mm) and Gram-positive bacteria Enterococcus faecalis (13 mm). The antioxidant activity of the synthesized AgNPs was investigated against the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and exhibited up to 61.21% ± 0.02% at an AgNPs concentration of 500 μg/mL.